Development of Learning Tools With Flipped Classroom Models to Train Critical Thinking Skills for 4th Grade Elementary School Students - Aliyatuz Zakiyah Darmawati; Raharjo; Utiyah Azizah (Indonesia Approach Education, 2023)
This development research aims to describe the validity, practicality, and effectiveness of Flipped Classroom Model Learning Devices to Train Critical Thinking Skills of Grade IV Elementary School Students. The learning tools developed are teaching modules, Student Worksheets (LKPD), Student Teaching Materials (BAPD), and Critical Thinking Tests. The method used is the Thiagarajan 4D Research and Development model: Define, Design, Develop, and Dessiminate. The same research was previously conducted using the 2013 curriculum, with research subjects ranging from high school to university students. In this research, the development of learning tools used an independent curriculum with the subject of fourth-grade elementary school students. Data collection techniques are carried out through validation, observation, and tests. The results showed that the Tools Validity Score (TVS)) for teaching modules had 3.64 very good criteria, student worksheet had 3.54 very good criteria, Student Teaching Materials had 3.73 very good criteria, and a critical thinking test had 3.66 very good criteria. The practicality of learning tools in terms of the implementation of learning by the teacher in the class obtained 97.25% very good criteria, and the activeness of students obtained 84.65% very good criteria. While the effectiveness of learning tools obtained from the N-Gain analysis of pretest and posttest results obtained 0.57 moderate criteria. The results obtained indicate that the learning tools developed are very feasible as learning media for fourth grade students.